Ileoileal intussusception due to Meckel's diverticulum in a pre-term neonate - Christopher Nemeh; Biruk Almaz; Victoria H. Ko; Abigail Walsh; Ryane Panasiti; Christopher A. Gitzelmann (Elsevier, 2023)
Presented is a case of ileoileal intussusception in a pre-term male born at 24 weeks gestation caused by a Meckel's diverticulum, which likely occurred in utero. Neonatal intussusception accounts for less than 1.3% of all intussusception cases and is exceedingly rare in premature infants [2]. Around 90% of pediatric intussusceptions involve the ileum telescoping into the cecum or ascending colon (ileocolic), however, ileoileal intussusception due to Meckel's diverticulum is less common [6]. The diagnosis of intussusception in the neonatal period requires a high index of suspicion and does not have any specific radiological findings or signs, in contrast to older children. Misdiagnosis leads to delay in treatment, which leads to intestinal perforation and necrosis [3]. Radiologic studies to help differentiate intussusception from other disease entities, including necrotizing enterocolitis (NEC). These studies include ultrasound, plain abdominal films, and air or contrast enema. Treatment of neonatal intussusception is primarily operative versus necrotizing enterocolitis (NEC) in which medical treatment can be considered initially. This case presentation reports an exceedingly rare cause of intestinal obstruction in a neonate and reminds clinicians to expand the differential diagnosis when consulted by the NICU.